Decoding peanut smut: A bibliometric analysis of two decades of research progress - Cazon, Luis Ignacio (2024)
Since its first detection in commercial peanut fields in 1995, both the prevalence and impact on yield of peanut smut disease, caused by the fungus Thecaphora frezzii, have increased significantly. Concurrently, diverse research groups have investigated the disease through various methodologies, enhancing our scientific knowledge base. This study was designed to collate and analyze the literature on peanut smut comprehensively, presenting a detailed scientometric analysis that traces the trajectory of research from the beginning to the current state. To achieve this goal, bibliographic data about the disease was compiled, and metrics were calculated. The analysis revealed that a small proportion of the scientific output was published in peer-reviewed journals, with epidemiology and breeding being the predominant topics. Collaborative efforts played a pivotal role in advancing the study of this disease. The study also pinpointed the most prolific researchers, participating institutions, and the influence of the published work, alongside other trends. However, despite notable progress in peanut smut research, this progress is insufficiently reflected in peer-reviewed literature, posing a challenge for researchers within this domain. Continued studies are vital for the integrated management of peanut smut, to mitigate further yield losses and prevent the pathogen's spread into new production regions.